Pendampingan Penyusunan Kartu Persediaan Bahan Baku Usaha UMKM Pabrik Tempe Bapak Ahmad Ramadhans Menggunakan Metode FIFO Perpetual - Neri Susanti; Nora Putri Fadila; Desi Ismawati; Eli Novita Sari; Ramadan Subhi (Universitas Dehasen Bengkulu, 2024)
Preparation of financial reports is one of the important things for a business especially UMKM business. But at the moment there are still lots of UMKM businesses that haven't been able to make financial reports properly and correctly. There are several factors that cause these MSME businesses to not make financial reports properly and correctly, one of which is their ignorance of accounting knowledge and they don't know where to start to make this good and correct financial report. Mr. Ahmad Ramadhans' Tempe factory is a business, UMKM factory, home-made tempeh by producing every day. Mr. Ahmad's tempeh factory is in the city of Bengkulu, but hasn't made financial reports properly and correctly. Therefore, we The Lecturer Service Team and Unived student accounting team provide training on making simple financial reports especially to record income and expenses which will produce a profit and loss report for the tempe factory Mr. Ahmad Ramadhans uses the FIFO Perpetual method where this method is in accordance with the tempe production of Mr. Ahmad, who produce and sell directly every day. The results of this service are very helpful for the owner of the tempe factory, Mr. Ahmad Ramadhans, in recording incoming and outgoing cash and knowing profit and loss properly and correctly.